PREVENTION IN PRIMARY CARE - INTRAFAMILIAL PREDICTIVE MODEL (IPM) - V. Herdea; R. Ghionaru; E. Costiug; I. Brinza; S.N. Rus; L. Comnea; E. Egri; E. Ruja; L. Chitanu; C.F. Pop; L. Soldea; A. Herdea; et al. (Amaltea Medical Publishing House, 2018)
The essence of the family medicine specialty remains surveillance of the health for the whole family: from pregnancy to child, from young to senior, from health to disease, from preventive to therapeutical interventions. The family doctor (GP) carries on two or even three generations of the same family, comes în contact with each family member, during many years of medical practice. The continuous clinical monitoring, will allow preparation of a "Risk Factors Map" (RFM). RFM is based on the high risk chronical pathology faced by a family over generations. Analising RFM and identifying major risk factors that act inside the family, GP can generate an intrafamilial predictive model (IPM). Having under medical care the whole family, developing în time a relationship of trust with the patients, based on serious profesional training, armed with good communication skils, GP has the possibility to implement personalized educational interventions inside the family for life style changing. This kind of intervention applied în early childhood, can slow down or delay the appearance and the evolution of the severe chronical diseases. În essence, IPM is an early preventive interventional mechanism în controlling the occurrence of major chronic diseases în future adults.